2003
DOI: 10.1016/s1359-4311(02)00194-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance investigation of plain and finned tube evaporatively cooled heat exchangers

Abstract: The performance of two evaporatively cooled heat exchangers is investigated under similar operating conditions of air flow rates and inlet hot water temperatures. The heat exchangers are plain and plate-finned circular tube types which occupy the same volume. Spray water, which is circulated in a closed circuit, is injected onto the exposed surfaces of the tubes and fins. The contact between air and spray water results in evaporative heat transfer. The tubes are copper, 10 mm o.d. The finned configuration is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…P. J. Erens [3] found that adding plastic filler into the core could improve the heat transfer property of common circular tube cooler and it could instead of high price finned tube by comparing several different forms of evaporative condenser core body performance. Hasan and Siren [4] compared the smooth circular closed cooling tower with finned circle closed cooling tower thermal performance to get a conclusion, Finned tube closed cooling tower of the heat and mass transfer coefficient is greater than the common round tube closed cooling tower; They also compared the smooth circular tube and oval tube closed cooling tower thermal performance in 2004, and got respectively suitable for the mass transfer experience formula through the data fitting, Oval tube closed cooling tower comprehensive performance coefficient is common round tube l. 93-1.96 times [5] . Thacker [6] designed a kind of closed cooling tower used in medium pressure nozzle, and test the spray density to provide the basis of closed cooling tower of the spray unit optimization design.…”
Section: Theoretical Research Of Abroadmentioning
confidence: 99%
“…P. J. Erens [3] found that adding plastic filler into the core could improve the heat transfer property of common circular tube cooler and it could instead of high price finned tube by comparing several different forms of evaporative condenser core body performance. Hasan and Siren [4] compared the smooth circular closed cooling tower with finned circle closed cooling tower thermal performance to get a conclusion, Finned tube closed cooling tower of the heat and mass transfer coefficient is greater than the common round tube closed cooling tower; They also compared the smooth circular tube and oval tube closed cooling tower thermal performance in 2004, and got respectively suitable for the mass transfer experience formula through the data fitting, Oval tube closed cooling tower comprehensive performance coefficient is common round tube l. 93-1.96 times [5] . Thacker [6] designed a kind of closed cooling tower used in medium pressure nozzle, and test the spray density to provide the basis of closed cooling tower of the spray unit optimization design.…”
Section: Theoretical Research Of Abroadmentioning
confidence: 99%
“…The thermal performance of closed towers has been the subject of a number of recent research projects undertaken by European Commission supported consortia, from which there are numerous associated publications [5][6][7][8][9][10][11]. Facao and Oliveira describe the development of a prototype closed cooling tower, specially adapted for use with chilled ceilings [5].…”
Section: Introductionmentioning
confidence: 99%
“…This allowed tower flow rates and tube configurations to be optimised on the basis of the cooling load thereby maximising the coefficient of performance. In further studies, the same authors examined the performance of two evaporatively cooled heat exchanger designs for a specially constructed small scale closed wet tower [8]. The heat exchangers utilised were plain and plate-finned circular tube types which occupied the same volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Sulaiman (2002) evaluated the performance of three natural fibers (palm fiber, jute and luffa) used as wetted pads in direct evaporative coolers. Hasan and Sirén (2003) investigated the performance of two evaporatively heat exchangers operating under similar conditions of air flow and inlet water temperatures This paper develops a mathematical model for direct evaporative cooling system and presents some experimental tests results in a direct evaporative cooler that take place in the Air Conditioning Laboratory at the University of Taubaté Mechanical Engineering Department, located in the city of Taubaté, State of São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 99%